Acquisition integration flexibility: toward a conceptual framework. Issue 4 (19th November 2018) - Schriber, Svante; King, David R.; Bauer, Florian
Abstract : Purpose: The purpose of this paper is to develop the role of integration flexibility as a mediator of acquisition performance and demonstrate how this capability varies across firms. Design/methodology/approach: The study develops a conceptual framework of anticipated relationships by building on existing but so far unintegrated acquisition research. Findings: The study suggests integration flexibility provides an explanation for variance in acquisition performance. The study identifies drivers behind acquisition integration flexibility in acquirer characteristics, deal characteristics and integration management. The authors further specify the positive and negative impact of several key factors commonly discussed in acquisition research. Research limitations/implications: Integration flexibility stands out as a novel explanation for acquisition performance. Still, the benefits from flexibility are not universal and developed logic suggests it represents a dynamic capability for acquirers. Our framework helps predict which acquirers and deals are more likely demonstrating this capability, thus contributing to predict acquisition performance. Practical implications: Acquisitions often take place in dynamic environments and reportedly often fail. Predicting and developing acquisition integration flexibility stands out as an important task for acquiring management. Social implications: Annual global acquisition values are on par with the GDP of large industrial nations (e.g. Germany) and failures for reasons of lacking acquisition integration flexibility contributes to value destruction harming not only firms, but society at large. Improved integration flexibility likely mediates this risk. Originality/value: Making an acquisition to adapt to environmental change implicitly assumes greater integration that can limit flexibility. While our argument builds on key concepts from acquisition research these so far have remained unconnected in relation to acquisition integration flexibility. The authors develop factors influencing this important capability and show how it mediates acquisition performance. This links acquisition antecedents with integration or phases typically treated separately.